The Effect Of Financial Literacy On Students' Behavior In Managing Finance (Case Study Of Students In Bandar Lampung) - Mahathir Muhammad; Defia Riski Anggarini; Berlintina Permatasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to examine the effect of the importance of financial literacy in terms of basic financial knowledge, financial attitudes, and financial behavior on student behavior in managing finances. The sample in this study were all students in Bandar Lampung with a total sample of 100 respondents from various universities in Bandar Lampung. Sampling using random sampling method. This type of research is quantitative using primary data and measurement using a Likert scale. The data analysis technique used is Multiple Linear Regression. The results showed that 1). Basic Knowledge of Finance has a negative and insignificant effect on Financial Management Behavior. 2). Financial attitude has a negative and insignificant effect on Financial Management Behavior. 3). Financial Behavior Has a Positive and Significant Effect on Financial Management Behavior.